IDT165 : Computer aided industrial design I / Faculty of Art and Design - UiTM, Faculty of Art and Design (Universiti Teknologi MARA (UiTM), 2023)
This course aims at introducing students to basic knowledge in digital 3D modeling and visualization. Students will learn about producing 3D modeling using computer-aided industrial design software. The design software is used in a wide variety of industries such as industrial design, CAD/CAM, rapid prototyping, reverse engineering, graphic design, and multimedia. In addition, the student will also learn how to create a 3D modeling and be rendering from technical drawing, sketches, real models, and written description by using a variety of 3D modeling methods. Apart from that, the student will be able to produce a high design using computer-aided industrial design as their tools to practice their design presentation.